Pengaruh Pemanfaatan Teknologi Informasi, Kompetensi Sumber Daya Manusia, Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Dengan Variabel Intervening Standar Akuntansi Pemerintahan Berbasis Akrual (Studi Empiris Di Pemda Kabupaten Barru) - Rasyidah Nadir; Hasyim Hasyim (AKUNTABEL, 2017)
This study aimed to examine the effect of the use of information technology, human resources and competencies on the quality of local government financial statements by the  accrual based government accounting standards  as interverning variable on the Government of Barru. Accrual accounting standards as defined in Regulation 71 of 2010 (PP No.71 Tahun 2010) concerning the Government Accounting Standards, and more technically set in Regulation 64 of 2013 (Permendagri No.64 Tahun 2013) concerning the Government Accounting Standards Implementation of Accrual Based On Local Government. The method used is descriptive survey. Samples were employees in the accounting / financial administration of the region on regional work units (SKPD) and Regional Financial Management Officer (PPKD) within the scope of local government Barru district. Methods of data collection is done by distributing questionnaires. Data were analyzed using path analysis. The results showed that the utilization of information technology have significant effect on the quality of financial statements Barru district government through the implementation of accrual based government accounting standards, while the competence of human resources has no significant effect on the quality of financial statements Barru district government through the implementation of accrual based government accounting standards.Keywords: Information Technology, Human Resources and   Competencies, Accrual Based Government Accounting Standards, Quality of Local Government Financial Statements.